(untitled) (Perspectivas em Ciência da Informação, 2013)
The text presents an interview with Michael Perelman, Professor at the Economics Department of California State University, Chico. The questions stimulate the interviewee to analyze the information age and especially some contradictions of the contemporary economy, which is supposed to be a knowledge intensive economy.